Jean Tirole: Mathematician-Economist-Humanist - Z. Mierzwa (Финансы: теория и практика, 2019)
Jean Tirole, the Nobel Prize winner in Economic Sciences in 2014, who in November 2018 visited the Financial university in Moscow, presents one of the most striking examples of the evolution currently experienced by some modern economists. He started his career as an economist at the time of rapid development of theories of regulation and competition policy. It was also the time of intensive development of industrial organisation (industrial economy), and especially its branch oriented to the public policy issues — economic regulation, antitrust law, and, more generally, economic governance of law in defning property rights, enforcing contracts, and providing organisational infrastructure. The progress in these areas reﬂected two methodological breakthroughs: the game theory and the theory of mechanism design. The widening use of game theory in industrial economics led to the migration of its achievements into other branches of microeconomics, such as behavioural economics and corporate fnance. In 1978, Jean Tirole left for the uSA to get a PhD in Economics at the Massachusetts Institute of Technology (MIT). He began his formation as an economist. The article tells about Jean Tirole’s way from an engineer and mathematician to the world-class economist. The author has paid special attention to the traditions of the French economic science, which had a considerable impact on the main areas of scientifc interests of Jean Tirole. Tirole’s managerial skills allowed to build an entire scientifc school around him both at the university of Toulouse and the Jean-Jaques Laffont Foundation, and in the newly formed Institute for Advanced Research.